Properties of SiO2 and Si3 N4 as gate dielectrics for printed ZnO transistors - Walther, Sabine; Polster, Sebastian; Meyer, Benedikt; Jank, M. P. M.; Ryssel, Heiner; Frey, Lothar (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics, 2011)
In this article, the authors report on thin film transistors based on gas phase synthesized ZnO nanoparticles using low temperature deposited silicon dioxide and silicon nitride as gate dielectrics. For bottom gate transistors, the devices using silicon nitride as gate insulator show the lowest off-current for a given induced charge and the steepest subthreshold slope. The charge carrier mobility of around 3×10-3 cm2/V s and an Ion/Ioff ratio of around 105 are almost independent of the insulator material. In a double gated thin film transistor using low stress silicon nitride as a top gate insulator, transistor parameters are extracted for the identical semiconducting layer when the bottom and top gates are used. It is shown that the extracted charge carrier mobility is not inherent for the ZnO nanoparticle layer but rather an effective value for the device under investigation.